Implementing nationally determined contributions: building energy policies in India's mitigation strategy. (9th March 2018) - Yu, Sha; Evans, Meredydd; Kyle, Page; Vu, Linh; Tan, Qing; Gupta, Ashu; Patel, Pralit
Abstract: The Nationally Determined Contributions are allowing countries to examine options for reducing emissions through a range of domestic policies. India, like many developing countries, has committed to reducing emissions through specific policies, including building energy codes. Here we assess the potential of these sectoral policies to help in achieving mitigation targets. Collectively, it is critically important to see the potential impact of such policies across developing countries in meeting national and global emission goals. Buildings accounted for around one third of global final energy use in 2010, and building energy consumption is expected to increase as income grows in developing countries. Using the Global Change Assessment Model, this study finds that implementing a range of energy efficiency policies robustly can reduce total Indian building energy use by 22% and lower total Indian carbon dioxide emissions by 9% in 2050 compared to the business-as-usual scenario. Among various policies, energy codes for new buildings can result in the most significant savings. For all building energy policies, well-coordinated, consistent implementation is critical, which requires coordination across different departments and agencies, improving capacity of stakeholders, and developing appropriate institutions to facilitate policy implementation.